Prawo do wolnych wyborów w Azerbejdżanie w świetle orzecznictwa Europejskiego Trybunału Praw Człowieka - Jastrzębski, Marcin (Wydawnictwo Uniwersytetu Rzeszowskiego, 2019)
The article provides an extensive analysis of the problem of the way how Azerbaijan implements international standards for free elections. The basic research mainly covers the jurisprudence of international bodies protecting individual rights, with a particular emphasis on the European Court of Human Rights and on the Council of Europe's Human Rights Commission, as well as the reports from observation missions of the OSCE elections of 2005 and 2010.
Right to free elections in Azerbaijan in the light of the case law of the European Court of Human Rights
Keywords: Azerbaijan; democracy; human rights; right to free elections; parliamentary mandate; member of parliament